Nomad Health : the disruption of physician staffing services - Licholai, Greg; Khalid, Ayesha N. (Ayesha Naz); Elias, Jaan (London : Yale School of Management, 2017)
In hospitals and practices there is a constant need for short-term doctors and nurses. The locum tenens agencies match doctors and nurses to hospitals in need of temporary staff. However, neither physicians nor hospitals were satisfied with the services existing brokers offered. The case outlines the creation of Nomad health by two neurosurgeons to provide a far more efficient and cheaper service in matching health care professionals to hospitals with labour shortages. The case invites the student to consider the difficulties of setting up Nomad Health and how the company could best gain advantages over its competitors.
Originally published in Licholia, G., Khalid, A. & Elias, J. (2017). Nomad Health: The disruption of physician staffing services. 17-013. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nomad Health -- Case studies; Medical personnel -- Employment -- Case studies; Labor supply -- Case studies